Control interno de inventario en el Ministerio de Agricultura y Ganadería de la ciudad de Babahoyo periodo 2020-2021. - Vargas Vargas, Génesis María (2022)
This research project is about analyzing the internal control of inventories in the Ministry of Agriculture and Livestock of the city of Babahoyo for the period 2020-2021, which determines the factors that in turn affect the fall of economic resources and a reduction of losses due to not having good control and precise handling. The purpose of this case study is to demonstrate the need and provide accurate information and insights for growing a business with good accounting results where decisions must be made to enable an organization to thrive in the environment resulting from the handling of goods used for commercialization of the company and maintain good inventory management where it will be verified if they have an effective control of the merchandise to obtain the necessary resources and satisfy the needs of the people. It is determined in the internal control of inventories that allows knowing the real order and the quantity of product specified correctly to avoid inconveniences in the entity, therefore, a qualitative methodology was used through an interview directed to the personnel in charge of the area. of inventories for the collection of data in describing the weaknesses in the internal control of inventories through suggestions, for this reason the established topic is related under the research subline of financial, tax and social commitment management. In this case study, a type of descriptive research was carried out where the observations, description, analysis of the entity are examined and finally the instruments were used as an interview guide to analyze doubts about the company.